2017
DOI: 10.1016/j.jart.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature ferromagnetism in Ni-doped TiO 2 diluted magnetic semiconductor thin films

Abstract: We report undoped and Ni-doped TiO 2 (x Ni = 0.00, 0.50, 1.00, 1.50, 2.00 and 2.50 wt.%) thin films fabricated on glass substrates by using a combination of solid-state reaction and dip coating techniques. The structural properties are observed by X-ray diffraction (XRD), which have depicted that annealing at 650 • C results in rutile Ni-doped TiO 2 as a major phase along with a minor anatase phase. The surface morphology of the deposited thin films, as measured by scanning electron microscopy (SEM), indicates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(17 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…6. The obtained curves revealed that the samples exhibited ferromagnetic behavior [46]. The graphs show typical hysteresis loops due to each specimen exhibiting coercivity and remanence (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…6. The obtained curves revealed that the samples exhibited ferromagnetic behavior [46]. The graphs show typical hysteresis loops due to each specimen exhibiting coercivity and remanence (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Many experimental studies have reported on the synthesis and the characterization of 3d TM-doped rutile TiO 2 materials. ,,,, ,,, Figure b sums up the domain limits of cationic species in this specific host material as proposed by Mizushima et al , based on experimental ( e.g. , photocurrent) and theoretical (semi-empirical model supported by photoconductivity and photo-ESR measurements) considerations.…”
Section: Resultsmentioning
confidence: 95%
“…These intentionally introduced point defects are well-known to create local structural distortions and in-gap electronic states, which may significantly modify the electronic, magnetic, and/or optical properties of host materials. In the case of the TiO 2 compound, the introduction of TM dopants has been reported to enhance photocatalytic, electrocatalytic, , or ferromagnetic properties but also to alter the irreversible anatase-to-rutile phase transition …”
Section: Introductionmentioning
confidence: 99%
“…It is well known that Ni ion is a more efficient dopant for TiO 2 , as it can improve electrical and magnetic properties. The reason for this enhancement has been tentatively ascribed to the suppression of electron-hole pair recombination on the surface of the TiO 2 catalyst by low valence Ni 2+ ions [34]. This upgraded activity was recognized as the enhanced separation of photo-generated electron-hole pairs due to the presence of Ni 2+ ions in TiO 2 [35].…”
Section: Introductionmentioning
confidence: 99%